Subranging BJT-Based CMOS Temperature Sensor With a ±0.45 °C Inaccuracy (3σ) From −50 °C to 180 °C and a Resolution-FoM of 7.2 pJ·K² at 150 °C - Bo Wang (86769) (2022)
This article presents a BJT-based CMOS temperature sensor with a wide sensing range from −50 °C to 180 °C. To effectively relax the sensor resolution requirement and conversion time over the entire temperature range to improve energy efficiency, we introduce a nonlinear subranging readout scheme together with double sampling to achieve dynamic reconfiguration of the sensor readout according to the ambient temperature. We further reduce the sensor power at high temperature by devoting the β -cancellation circuit only for BJT biasing while applying a temperature-independent bias current for the other sensor building blocks. Implemented in 0.18- μ \text{m} CMOS with four-wire connections and switch-leakage compensation based on small BJTs, the proposed sensor chip prototype achieves a high resolution-FoM of 7.2 pJ · \text{K}^{{2}} at 150 °C, while featuring a small sensing error of ±0.45 °C under a 1.5-V supply. Other Information Published in: IEEE Journal of Solid-State Circuits License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/jssc.2022.3208770